Active Region-Based Full-Disc Solar Image Hashing - Grycuk, Rafał; Costa, Kelton [UNESP]; Scherer, Rafał (Springer Nature, 2020)
The main components of the Solar activity are solar flares, coronal mass ejections, high-speed solar wind, and solar energetic particles. Solar flares impact the Earth when they occur on the side facing our planet.
Keywords: CBIR; Solar activity analysis; Solar hash; Solar image description